A metabolite profiling method for diagnosis of precancerous cervical lesions and HPV persistence. (April 2017) - Walker, Heather; Burrell, Michael; Flatley, Janet; Powers, Hilary
Aim: With the advent of rapid metabolic profiling techniques and of portable mass spectrometers we examined whether cells distinguished by their cytology and persistence of human papillomavirus infection, could be easily differentiated by their metabolite profile.Materials & methods: Direct injection electrospray mass spectrometry was used in a nontargeted double-blind experiment. Samples were collected from women diagnosed with one of two grades of cervical cytology and exhibiting either human papilloma virus persistence or clearance. Cell extracts were prepared using a DNA extraction procedure and the resulting supernatant, normally discarded, was analyzed. Data were interpreted using principal component analysis.Results: The results indicate strongly that a simple metabolite profiling method could be used to rapidly identify women at increased risk of cervical cancer.